Corporate insolvency : separate legal personality and directors' duties to creditors / Mohammad Rizal Salim - Salim, Mohammad Rizal (Faculty of Administratron and Law, 2004)
The primary purpose for the doctrine of separate legal personality is to encourage entrepreneurship, by shifting the risks of business failure away from entrepreneurs to creditors and other risk bearers. Unfortunately this doctrine is subject to abuse by corporate controllers, which prompted the courts and the legislature to provide for exceptions. These exceptions are better known as the lifting or piercing of the corporate veil. How do these exceptions protect creditors? How effective are they? This article seeks to examine laws in relation to the separate legal personality doctrine and the duties of directors which directly affects, or attempts to protect, creditors from unfair and improper conduct by corporate controllers.